Economic and Technical Feasibility of Waste-to-Energy Conversion for Pollution Control - Sakshi Tyagi (International Journal of Environmental Noise and Pollution Control, 2023)
This review study explores waste-to-energy (WtE) conversion's technical and economic viability as a pollution management strategy. The paper presents a critical review of WtE technologies and their potential contributions to pollution reduction considering the urgent need for sustainable waste management in the face of rising environmental issues. The evaluation of the literature includes a thorough investigation of WtE technologies and their development over time. Understanding the technological capabilities of different WtE technologies and their efficiency in decreasing environmental pollutants is prioritized. The analysis of cost structures, income generating methods, and comparative cost-benefit assessments in the context of pollution management are all included in the review's economic aspects section. An analysis of the effectiveness, adaptability, and environmental performance of WtE technologies is used to determine technical feasibility. This assessment is supported by a review of emissions control strategies, which evaluates their capacity to reduce greenhouse gas emissions as well as air and water pollution. This review highlights the waste-to-energy conversion's versatile potential as a workable environmental protection strategy. It emphasizes the significance of a comprehensive assessment that incorporates technical as well as financial variables into the decision-making process. Policymakers, researchers, and practitioners who are devoted to reducing pollution while utilizing the energy-producing potential that waste materials can benefit greatly from the insights gained from this paper, which informs conversations on sustainable waste management techniques.
Keywords: Economic feasibility; Environmental sustainability; Feasibility assessment; Pollution control; Waste-to-Energy (WtE); technical feasibility